PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KERJA KARYAWAN CV. MODERN OPTIK CIREBON - Rahmat Riadi, Ade; Yanuarti, Maghfiroh (Journal of Research and Publication Innovation, 2024)
The aim of the research is to determine the influence of the physical work environment and work discipline on employee performance at CV Modern Optik Cirebon, both partially and simultaneously. The method used is quantitative with the population of this research being all 80 employees in the office. The sampling method uses a saturated sampling technique, so that the entire population is sampled. The analytical method in data management is validity testing, reliability testing, classical assumption testing, linear regression testing, correlation coefficient testing, coefficient of determination testing, and hypothesis testing. The results of this research show that there is an influence of the physical work environment on employee performance as shown by the calculated t value (13.222) > t table (1.991) and the significance value (0.000 < 0.05) in linear regression, namely Y = 7.509 + 0.799X1, test the coefficient of determination is 0.751 or 75.1%, the correlation coefficient is 0.867, where the physical work environment on employee performance has a very strong level of relationship strength. There is an influence of work discipline on employee performance as shown by the calculated t value (16.704) > t table (1.991) and the significance value (0.000 < 0.05) in the linear regression, namely Y = 15.424 + 0.654X2, the coefficient of determination is 0.828 or 82.8 %, the correlation coefficient is 0.910, where work discipline and employee performance have a very strong level of relationship strength. And there is an influence between the work environment and work discipline on employee performance as shown by the results of the f test which simultaneously obtained calculated f (69.543)> f table of (3.115) with a significance value of (0.000 < 0.05) in multiple linear regression Y = 13.129 + 0.172X1+ 0.531X2, coefficient of determination of 0.833 or 83.3%, correlation coefficient of 0.913, where the physical work environment and work discipline on employee performance have a very strong level of relationship strength.